Evaluating the Structural Performance and Durability of CNT and Polyethylene Fiber-Reinforced Concrete - Al Araj, Rashad R. (2016)
A Master of Science thesis in Civil Engineering by Rashad R. Al Araj entitled, "Evaluating the Structural Performance and Durability of CNT and Polyethylene Fiber-Reinforced Concrete," submitted in November 2016. Thesis advisor is Dr. Adil Al-Tamimi and thesis co-advisor is Dr. Noha Hussein. Soft and hard copy available.